1998
DOI: 10.1074/jbc.273.23.14566
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling by Cyclic ADP-ribose, NAADP, and Inositol Trisphosphate Are Involved in Distinct Functions in Ascidian Oocytes

Abstract: ADP-ribosyl cyclase catalyzes the synthesis of two structurally and functionally different Ca 2؉ releasing molecules, cyclic ADP-ribose (cADPR) from ␤-NAD and nicotinic acid-adenine dinucleotide phosphate (NAADP) from ␤-NADP. Their Ca 2؉ -mobilizing effects in ascidian oocytes were characterized in connection with that induced by inositol 1,4,5-trisphosphate (InsP 3 ). Fertilization of the oocyte is accompanied by a decrease in the oocyte Ca 2؉ current and an increase in membrane capacitance due to the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
75
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 43 publications
8
75
1
Order By: Relevance
“…This self-inactivation phenomenon of NAADP-induced Ca 2ϩ release after Ca 2ϩ signaling during fertilization suggests that NAADP plays a physiological role in the fertilization process (18). Inhibition of fertilization-associated membrane expansion in ascidian oocytes by NAADP led to a similar conclusion (19). Mammalian systems contain the enzymatic machinery to synthesize and degrade NAADP (11,20), and the presence of endogenous NAADP has been inferred in Arabidopsis thaliana with desensitization experiments (2).…”
mentioning
confidence: 66%
“…This self-inactivation phenomenon of NAADP-induced Ca 2ϩ release after Ca 2ϩ signaling during fertilization suggests that NAADP plays a physiological role in the fertilization process (18). Inhibition of fertilization-associated membrane expansion in ascidian oocytes by NAADP led to a similar conclusion (19). Mammalian systems contain the enzymatic machinery to synthesize and degrade NAADP (11,20), and the presence of endogenous NAADP has been inferred in Arabidopsis thaliana with desensitization experiments (2).…”
mentioning
confidence: 66%
“…1 To whom correspondence should be addressed (e-mail sandip.patel!pharmacology.oxford.ac.uk). Although the effects of NAADP have been most extensively characterized in sea urchin eggs, recent studies have extended the actions of NAADP to ascidian [14] and starfish [15] oocytes, mouse pancreatic acinar cells [16,17], rat brain microsomes [18], and plant preparations [19]. These studies strongly support a general role for NAADP-mediated Ca# + signalling.…”
Section: Introductionmentioning
confidence: 90%
“…NAADP and RyR pathways would be involved only in the generation of localised Ca 2+ signals in the cortex of the egg. The RyR mediated Ca 2+ signal is necessary for new membrane insertion whereas the physiological significance of NAADP induced Ca 2+ release remains unknown (Albrieux et al, 1998;Albrieux et al, 2000). As every meiotic Ca 2+ wave in the ascidian starts from the cortex where these receptors are presumably located, it is possible that RyR and NAADP participate somehow in the initiation of the global Ca 2+ wave in the egg.…”
Section: The Ca 2+ Signalling Machinery Of the Eggmentioning
confidence: 99%
“…In addition, even though Ca 2+ influx may occur during the operation of the pacemakers, it has been shown that the second phase of Ca 2+ oscillations does not require external Ca 2+ (Sensui and Morisawa 1996;Carroll et al, 2003) raising the question of the physiological significance of Ca 2+ influx into the fertilised egg. A 40 % increase in plasma membrane area takes place at fertilisation and microvilli grow during the establishment of the contraction pole (Albrieux et al, 1998;Albrieux et al, 2000;Sardet et al, 2002). There is no cortical granule exocytosis in ascidian eggs and it is not known which intracellular membranous organelle fuses with the plasma membrane.…”
Section: The Ca 2+ Signalling Machinery Of the Eggmentioning
confidence: 99%
See 1 more Smart Citation